Quantitative CNV testing in molecular diagnostics - Somerville, Martin (Henry Stewart Talks, 2009)
Copy number variants, and the history of genomic rearrangements and disease, Methods used for copy number variant detection, Criteria to determine whether or not a copy number variant is associated with disease, Application of these criteria in molecular diagnostics, with examples of novel copy number variants
Archived at 2021/07/28